Implications Of Work Discipline And Organizational Commitment To Employee Performance With Motivation As An Intervening Variable At University Development Of Panca Budi Medan - Raysa Vionika; Nizamuddin; Wilchan Robain (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze the relationship between work discipline, organizational commitment, employee performance, and work motivation with work motivation as an intervening variable at Panca Budi Medan Development University. The results showed that work discipline had a significant positive influence on employee performance (O = 0.818, T-statistics = 5.953, P-value = 0.000) but not significantly on work motivation (O = 0.353, T-statistics = 1.235, P-value = 0.217). Employee performance had a significant positive effect on work motivation (O = 0.73, T-statistics = 2.804, P-value = 0.005). On the other hand, organizational commitment did not have a significant effect on employee performance (O = 0.152, T-statistics = 1.124, P-value = 0.261) or work motivation (O = -0.174, T-statistics = 0.967, P-value = 0.443). Work motivation was proven to be a significant mediator in the relationship between organizational commitment and employee performance (O = 0.597, T-statistics = 2.521, P-value = 0.012). This research highlights the importance of work discipline and motivation as a liaison in improving employee performance.